Dynamic stability of ethylene-vinyl acetate copolymer/crumb rubber modified asphalt. (15th December 2017) - Yu, Ruien; Liu, Xiaolong; Zhang, Maorong; Zhu, Xijing; Fang, Changqing
Graphical abstract: Highlights: Dynamic stability is considered for EVA/CR modified asphalt. Morphology variation of modified asphalt samples in the preparation process is observed. AFM is used to reveal the stabilization mechanism of polymer modified asphalt. Abstract: In this paper, the recovered waste packaging ethylene-vinyl acetate copolymer (EVA) and crumb rubber (CR) were used as polymer modifying agents to prepare EVA/CR modified asphalt, and the EVA/CR modified asphalt's dynamic stability were studied. After characterized and analyzed with conventional physical performance test, differential scanning calorimetry (DSC) and Fourier transform infrared spectroscopy (FTIR), it can be found that the macro and micro properties of modified asphalt in the process of modification modified asphalt evolved from an unstable state to a dynamic stable state and until to a completely final stable state after removed the shear force. The polymer particles gradually dispersed evenly in the modified asphalt and a cross-linked polymer network structure was formed during the shearing process, which were clearly showed through the fluorescence microscopy images. Finally, the interaction between the polymer modifying agents and base asphalt and its impact to the properties of the system were also analyzed combining macro, micro properties of modified asphalt and the morphology changes of modifier and asphaltenes. In addition, stabilization mechanism of EVA/CR modified asphalt was revealed through the former analysis.